2004
DOI: 10.2527/2004.82113189x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary iron supplementation on growth performance, hematological status, and whole-body mineral concentrations of nursery pigs1

Abstract: An experiment was conducted to evaluate the effects of supplementing increasing concentrations of Fe to the diet of nursery pigs on growth performance and indices of hematological and mineral status. Pigs (n = 225; 6.5 kg; 19 +/- 3 d) were allotted randomly by BW, litter, and gender to one of five dietary treatments (five pigs per pen; nine pens per treatment). Basal diets for each phase (Phase 1: d 0 to 7; Phase 2: d 7 to 21; Phase 3: d 21 to 35) were formulated to contain minimal Fe concentration and then su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
57
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 31 publications
17
57
0
1
Order By: Relevance
“…The hepatic Fe stores of the newborn piglet combined with the low Fe concentration in sows' milk are not sufficient to meet the pig's Fe need for rapid growth and increase in blood volume (88) . Consequently, the use of exogenous sources of Fe to prevent Fe deficiency in neonatal pigs has been well documented (89,90) .…”
Section: Biological Effects Of Dietary Nucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatic Fe stores of the newborn piglet combined with the low Fe concentration in sows' milk are not sufficient to meet the pig's Fe need for rapid growth and increase in blood volume (88) . Consequently, the use of exogenous sources of Fe to prevent Fe deficiency in neonatal pigs has been well documented (89,90) .…”
Section: Biological Effects Of Dietary Nucleotidesmentioning
confidence: 99%
“…Consequently, the use of exogenous sources of Fe to prevent Fe deficiency in neonatal pigs has been well documented (89,90) . However, the bioavailability of Fe from different sources may vary considerably (91,92) , and, according to Rincker et al (88) , is not only dependent on the Fe status of the animal but also on dietary Fe as well as on various nutritional and non-nutritional substances within the diet. Dietary nucleotides, particularly the degradation product of IMP, inosine, might play a role in facilitating intestinal Fe absorption (93) .…”
Section: Biological Effects Of Dietary Nucleotidesmentioning
confidence: 99%
“…Increases in pig liver iron levels with increasing levels of supplementation, demonstrating a high storage capacity of that organ, have been noted by several authors (FURUGOURI, 1972a;RINCKER et al, 2004;YU;HUANG;CHIOU, 2000) but not observed in this experiment.…”
Section: Resultsmentioning
confidence: 50%
“…Estes dados correspondem aos obtidos por outros autores, quando observaram que a redução de ferro nas rações não alterou o ganho de peso dos animais em fase de crescimento alimentados com a mesma fonte de ferro em diferentes concentrações (Amine et al, 1972). Essas observações foram destacadas em estudos com leitões após o desmame (Yu et al, 2000;Rincker et al, 2004).…”
Section: Resultsunclassified